Antifibrinolytic Therapy in Intracranial Hemorrhage. Issue 7 (21st October 2013) - Meier, Kevin; Hoesch, Robert; Gurwitz, David
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Preclinical Research </table-wrap> Treatment options for intracranial hemorrhage include surgery, blood pressure control, and hemostatic medications. Antifibrinolytics are hemostatic medications that interrupt the pathway leading to the breakdown of fibrin clots, thereby stabilizing the latter. The primary antifibrinolytics in use are tranexamic acid and epsilon‐aminocaproic acid, both of which are lysine analogs. These medications have been used with some success in cardiac surgery, trauma, and menorrhagia. In the intracranial hemorrhage literature, antifibrinolytics have been studied mostly in aneurysmal subarachnoid hemorrhage. While early trials in subarachnoid hemorrhage showed decreased rebleeding rates with consequently increased risk of stroke, newer studies using medical vasospasm prevention and shorter treatment durations have demonstrated a potential for clinical utility. There are also data supporting the use of antifibrinolytics in traumatic brain injury. Antifibrinolytics are less promising agents for hemostasis in subdural, epidural, and intraparenchymal hemorrhages.